Reforma slovenske regionalne politike - Kavaš, Damjan (Geographica Slovenica, 2000)
Stimulation of regional development is representing, due to economic, social, spatial and also political reasons, an important part of the national economic policy of developed countries. Therefore in the year 1998 Slovenia joined the reform of regional policy, which results in the regional structural policy, introducing a new system for stimulation of the regional development. The least is in accordance with the developmental policy in well-developed countries however the construction of the system in whole shall require some additional time.
Keywords: regionalni razvoj; regionalna politika; regije; ekonomski razvoj; regionalno gospodarstvo; Slovenia; Slovenija; Europe; Evropa; Evropska unija; European Union